Spatial Cognition VIII International Conference, Spatial Cognition 2012, Kloster Seeon, Germany, August 31 -- September 3, 2012, Proceedings - Stachniss, Cyrill; Schill, Kerstin; Uttal, David (Lecture Notes in Artificial Intelligence, 2012)
This book constitutes the proceedings of the 8th International Conference on Spatial Cognition, SC 2012, held in Kloster Seeon, Germany, in August/September 2012. The 31 papers presented in this volume were carefully reviewed and selected from 59 submissions. The conference deals with spatial cognition, biological inspired systems, spatial learning, communication, robotics, and perception.